Hypertransaminasemia in severely malnourished adult anorexia nervosa patients: Risk factors and evolution under enteral nutrition - Hanachi, Mouna; Melchior, Jean Claude; Crenn, Pascal (Clinical nutrition (Edinburgh, Scotland), 2013)
Aminotransferase abnormalities have been reported in malnourished patients with anorexia nervosa (AN). The aim of this study was to identify prevalence and risk factors of hyperaminotransferasemia in an adult cohort of AN patients and to describe evolution during nutritional rehabilitation with enteral nutrition for a period of 4 weeks. Retrospective study of all consecutive malnourished (BMI <16) AN adult patients, without previous liver diseases or hepatotoxic drugs or alcohol consumption, hospitalized for enteral nutrition in a single center between 1998 and 2008. Hypertransaminasemia was defined by an increase in AST and (or) ALT >2N. In all, 126 AN patients (117 W, 9 M), age 30 ± 10.8 years, were included. At admission, 54 (43%) patients presented hypertransaminasemia. In univariate analysis, risk factors for hypertransaminasemia were: lower BMI (11.2 ± 2 vs. 13 ± 2, p < 0.0001) and age (28 ± 9 vs. 32 ± 12, p < 0.05), male sex (p < 0.05) and the pure restrictive form (p = 0.07). In multivariate analysis only BMI, at a threshold of 12, remained significant [OR 3.7, CI: 95% 2.24–5.2]. Normalization of aminotransferases at the end of week 4 of enteral nutrition was obtained in 96%. Only 2/54 patients (4%) presented a worsening of aminotransferases during the refeeding period, including one that died of liver failure. None of the patients without hypertransaminasemia admission presented a subsequent elevation. At the end of the 4-week refeeding period, the increase in BMI was greater in patients without hypertransaminasemia than in those with it (2.0 ± 0.8 vs. 1.5 ± 1.0, p < 0.0001). Elevated transaminases is common in severe malnourished AN patients. Four risk factors were identified: young age, low BMI (the only independent factor in multivariate analysis), the pure restrictive form of the disease and male sex. After 4 weeks of enteral nutrition the evolution is in most cases favourable, albeit with a lower increase in BMI, but can be severe. The long-term evolution remains to be determined.